Simple beginnings : beading - Wilson, Suzann Sladcik (Design Originals, 2012)
"Beading is a fun craft that can produce beautiful custom pieces for every occasion imaginable, but if you've never tried to make your own necklaces bracelets, the task can seem a little daunting. What type of fasteners are best to use? Where can you find the best materials to work with? And just what can you create once you have everything you need? In Simple Beginnings in Beading, renowned artist Suzann Sladcik Wilson will put all these questions to rest. Wilson will take you to the very beginning of the beading process and teach you about the tools you will need and the materials you should buy. Then, she will take you step-by-step through the basic beading techniques you will need to know to create your own works of art. Projects for beginner, intermediate, and advanced craft enthusiasts are included, ensuring that you'll always have something new to inspire and create as your skills increase. Use this book to make bracelets, necklaces, watches, earrings, and more, all in your own unique, creative style. Get started today!"--